Flight from Grace A Cultural History of Humans and Birds. - Pope, Richard (McGill-Queen's University Press, 2021)
Suggesting that the replacement of an animistic worldview with a mechanistic one has led humans to deny their animality, Flight from Grace calls on readers to appreciate how our past relationship with birds might help transform our current relationship with nature.